ADDRESSING THE SPIRITUAL CRISIS OF GENERATION Z: INSIGHTS AND STRATEGIES FOR ISLAMIC EDUCATIONAL INSTITUTIONS - Yahya, Ahmad Firdaus Nur; Ardita, Norma; Muminah, Fadlilatul; Lailinda, Ika Auliya Nur (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2026)
The phenomenon of spiritual crisis among Generation Z, particularly in Islamic education settings, is becoming increasingly prominent as a result of technological developments and growing social pressures. This crisis leads to a loss of direction in life, emotional instability, and decreased participation in religious activities. This raises the need to explore the factors influencing students' spirituality and effective strategies for reawakening their spiritual awareness. This study aims to identify the forms of spiritual crisis experienced by students at MA NU Nurussalam, analyze the factors contributing to their weak spirituality, and formulate effective spiritual development strategies. Using a descriptive qualitative approach, data were collected through in-depth interviews with the principal, teachers, and students. The results indicate that students' spiritual crisis is influenced by internal factors such as lack of motivation and self-awareness, as well as external factors such as academic pressure and the influence of social media. Proposed strategies for rebuilding spiritual awareness include a more contextual approach to religious education, empowering teachers as spiritual role models, and organizing interactive spiritual activities. This study makes an important contribution to understanding the spiritual crisis in Islamic education and offers practical solutions for enhancing students' spirituality in the digital era.